Conventional and Holter Electrocardiographic Assessment of Dogs Infected Naturally With Acute Canine Monocytic Ehrlichiosis - de Castro Ferreira Lima, Mayra [UNESP]; Bornhousen Cardoso de Araújo, Juliana [UNESP]; Paes, Antonio Carlos [UNESP]; Gianfrancesco Filippi, Mauricio [UNESP]; Cruz-Aleixo, Amanda Sarita [UNESP]; Kiomi Takahira, Regina [UNESP]; Gomes Lourenço, Maria Lucia [UNESP] (Elsevier, 2019)
Canine Monocytic Ehrlichiosis (CME) is a disease of worldwide distribution caused by the bacteria Ehrlichia canis, appearing primarily in hot climates due to the massive prevalence of its vector, the tick Rhipicephalus sanguineus. Previous studies have shown that dogs afflicted by CME in the chronic phase can develop infectious myocarditis, arrhythmias, and alterations in heart rate variability (HRV), but there are few studies correlating cardiac diseases with the acute phase of CME. This study aims at assessing electric cardiac alterations and HRV in the time and frequency domains during the acute phase of CME. This study assessed 22 animals divided into 2 distinct groups: the control group, comprised by 10 healthy dogs, and the sick group, comprised of 12 dogs infected naturally with ehrlichiosis which presented clinical and hematological signs compatible with the acute phase of the disease. The animals underwent conventional and Holter electrocardiographic evaluations, systolic blood pressure measurement, complete blood count and biochemical assays (urea, creatinine, alanine aminotransferase (ALT), alkaline phosphatase (AP), and gamma glutamyl transferase (GGT)). The sick group presented higher activity in the sympathetic nervous system than in the parasympathetic nervous system, manifest as a significant increase in mean heart rate and a reduction in the HRV indexes for the time and frequency domains. The frequency-domain HRV indexes presented sympathetic prevalence during the sleep and vigilance states. Sinus tachycardia was the predominant heart rhythm in 58.33% of the animals. The mean systolic blood pressure diverged between the groups and no significant arrhythmias were observed during monitoring. The serum concentrations of urea, creatinine, AP, ALT, and GGT were within the established reference values for the species. We observed no indication that there was enough time during the acute phase for the disease to evolve in a way that resulted in arrhythmias, as is common in the chronic phase, but we observed that animals in the acute phase already present reduced HRV indexes.
Keywords: autonomic tonus; dogs; heart rate variability; myocarditis